American beauty ... sehen Sie genau hin - Spacey, Kevin 1959-; Bening, Annette 1958-; Birch, Thora 1982-; Ball, Alan 1957-; Hall, Conrad Lee 1926-2003 (DreamWorks, 2000)
Lester Burnham, a depressed suburban father in a mid-life crisis, decides to turn his hectic life around after developing an infatuation for his daughter's attractive friend. (Internet Movie Database)
Original: USA 1999
Bildformat: 2.35:1 anamorphic widescreen
Zusatzmaterial: Hinter den Kulissen; Kurzfeature; Audiokommentar mit Regisseur Sam Mendes und Drehbuchautor Alan Ball; Storyboard präsentation mit Sam Mendes und Kameramann Conrad L. Hall; 2 Original-Kinotrailer
5 Oscars 1999 ! inklusive Bester Film
Keywords: Altern; Junge Frau; Mann; Sexualität; USA; Film; DVD-Video